Adaptive Coping Stabilizes Post Divorce Adjustment in Young Adults - Prabandari, Novita; Widiantoro, Fx. Wahyu (Academia Open, 2026)
General Background: Divorce during early adulthood can generate substantial psychological, social, and economic challenges because this life stage involves identity formation, financial independence, and the development of stable intimate relationships. Specific Background: The study examined post-divorce experiences among individuals aged 26–30 who faced emotional distress, social stigma, economic pressure, identity disruption, and changing family responsibilities after marital separation. Knowledge Gap: Although divorce has been widely discussed, limited qualitative attention has been given to how early adults interpret lived experiences and construct adjustment strategies after divorce. Aims: This study aimed to explore post-divorce experiences and adjustment strategies among early adults through an interpretive phenomenological perspective. Results: The findings showed that all participants experienced sadness, anger, disappointment, loss, and psychological distress in the initial post-divorce period. Social stigma associated with being a young widow affected self-esteem and social engagement, while economic demands created both financial autonomy and added burdens, especially for participants with children. Participants who used adaptive strategies, including work focus, spirituality, physical activity, financial independence, counseling, and active social support, demonstrated more stable recovery, whereas passive or maladaptive strategies were linked to slower or fluctuating adjustment. Novelty: The study identifies post-divorce adjustment as a dynamic process shaped by emotional regulation, social support, economic conditions, children, stigma, and identity reconstruction. Implications: The findings indicate the need for comprehensive psychological assistance that integrates counseling, social support strengthening, financial guidance, emotional regulation, and identity reconstruction for early adults after divorce. Highlights: Emotional distress appeared strongly in the early separation period. Family, friends, and professional services functioned as protective resources. Stigma, financial demands, and parenting responsibilities shaped recovery patterns. Keywords: Divorce, Early Adulthood, Self-Adjustment, Phenomenology, Coping Strategies, Social Support